2020
DOI: 10.3390/cosmetics7030065
|View full text |Cite
|
Sign up to set email alerts
|

An Uncontrolled Case Series Using a Botanically Derived, β-Cyclodextrin Inclusion Complex in Two Androgenetic Alopecia-Affected Male Subjects

Abstract: Drug-based monotherapy provides limited clinical benefits in polygenic disorders, such as androgenetic alopecia. Possible benefits must be measured against non-trivial risks of negative side effects. Several well-controlled, peer-reviewed, basic science studies have demonstrated novel mechanisms of action and potential utility for natural-based phytochemicals in the treatment of androgen-mediated disorders, including androgenetic alopecia. Yet, due to phytochemical instability, volatility, and incompatibility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…After 270 days of treatment, there was no evidence of hair loss in the study subjects. The study suggested that a plant-based, nano-complexed formula could be a supportive treatment strategy for androgenetic alopecia and drug-based treatments [ 89 ]. Leaves and roots of Arctium lappa L. are used to treat skin inflammation, promote wound healing, act against dandruff, and prevent hair loss [ 90 ].…”
Section: Role Of Phytochemicals In Managing Hair Lossmentioning
confidence: 99%
“…After 270 days of treatment, there was no evidence of hair loss in the study subjects. The study suggested that a plant-based, nano-complexed formula could be a supportive treatment strategy for androgenetic alopecia and drug-based treatments [ 89 ]. Leaves and roots of Arctium lappa L. are used to treat skin inflammation, promote wound healing, act against dandruff, and prevent hair loss [ 90 ].…”
Section: Role Of Phytochemicals In Managing Hair Lossmentioning
confidence: 99%